Campaña publicitaria de lanzamiento para la nueva cadena de cafetería peruana Atemporal - Floriano Alarcon, Maria Alexandra (2023)
This professional work consists in the launch campaign of the new Peruvian cafeteria chain: Atemporal, with the objectives of achieving a viable, profitable, and memorable campaign. To achieve this, a market study of the sector was conducted, as well as the definition of its target audience, value proposition, and positioning, with the aim of achieving a coherent campaign that aims to introduce the brand and position it in the market through the creation of its visual identity, a strategy, ideas, tactics, and a media plan. To achieve this, a qualitative and quantitative analysis was used to help achieve the expected results.